The effect of digital banking trends on the growth of banking fee-based income - Novi Handayani Simbolon (Institute of Computer Science (IOCS), 2023)
The development of information technology which is very significant in the current 4.0 revolution era is increasingly directing the creation of changes in consumption patterns in people's lives that are moving towards digital, thus encouraging the banking industry to accelerate the transformation into digital banks that are packaged and developed with the aim of providing fast and fully accessible services independently by customers while still prioritizing the principle of security over the confidentiality of personal data optimized through digital technology systems by issuing digital banking services. This study aims to determine the effect of digital banking trends on the growth of banking fee-based income in Indonesia through a quantitative data analysis process obtained through secondary data documentation techniques through the website of each bank which is then processed using the help of the Eviews 10 program through panel data regression tests. The population in this study were all Persero Banks in Indonesia for the period 2018 to 2022, totaling 5 banks. The sample selection was carried out using purposive sampling technique and it was found that only 4 banks met the criteria, so the number of observations in this study was 20 observations. Based on data processing, the research results state that both mobile banking services, payment gateway services, and QRIS services have a significant positive effect on the growth of fee-based income of Bank Persero in Indonesia for the period 2018 to 2022